Yearly changes in the anthropometric dimensions of female high school gymnasts - Zuniga, J.; Housh, T.; Camic, C. L.; Mielke, M.; Hendrix, C. R.; Johnson, G. O.; Housh, D. J.; Schmidt, R. J. (The Journal of Strength and Conditioning Research, 2011)
The purpose of the present study was to compare the age-related patterns of anthropometric dimensions of female high school gymnasts to those of a national representative sample of teenage girls. One hundred and one female high school gymnasts (X ± SD age = 15.8 ± 1.1 year; height [HT] = 162.2 ± 5.7 cm; body weight [BW] = 54.1 ± 6.5 kg) volunteered as subjects in the present study. The sample was divided into 4 independent age groups: age group 14 (AG14) = 14.00 to 14.99 years (n = 26); AG15 = 15.00 to 15.99 years (n = 27); AG16 = 16.00 to 16.99 years (n = 29); and AG17 = 17.00 to 17.99 years (n = 19). Nine variables including BW; HT; body mass index (BMI); subscapular and triceps skinfolds; and waist, mid-arm, maximal calf, and mid-thigh circumferences were assessed on each subject. Independent t-tests indicated that for all age groups, the female high school gymnasts exhibited lower BW, BMI, circumferences (waist, mid-arm, maximal calf, and mid-thigh) and skinfolds (subscapular and triceps) than the national sample, except AG 17 for BW and maximal calf and mid-thigh circumferences. There were no significant differences in HT between samples for any of the age groups. Furthermore, there were no differences between the high school gymnasts and the national sample for the slope coefficients for the anthropometric dimensions vs. age relationships. These findings indicated that in females, participation in high school gymnastics does not adversely affect yearly changes in anthropometric dimensions.